Pendekatan Integratif Sains Dan Agama Pada Pembelajaran PAI Dalam Membentuk Karakter Islami Peserta Didik - Ainun Nida Miladiyah; Moh. Irmawan Jauhari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The significance of using an integrated approach to science and religion in Islamic Religious Education instruction in shaping and developing students’ character serves as the driving force behind this research. The author employed case study methodology along with qualitative research in this work. The investigation’s findings demonstrated how Islamic Religious Education is putting science and religion into practice through internal and external integrative methods of learning. Memorisation of brief letters, reading aloud from the Qur’an, memorising and reciting Asmaul Husna, daily prayers, tadarrus (reading the holy book together), and literacy exercises are all examples of internal integration that help pupils develop their character. While kids character is developed via everyday routines and activities, science and religion are externally integrated.